FGFR4 Arg388 genotype is associated with pathological complete response to neoadjuvant chemotherapy for primary breast cancer - Marmé, Frederik; Werft, Wiebke; Benner, Axel; Burwinkel, Barbara; Sinn, Peter; Sohn, Christof; Lichter, Peter; Hahn, Meinhard; Schneeweiss, Andreas (Annals of oncology, 2010)
A single-nucleotide polymorphism (SNP) in the FGFR4 gene is associated with poor prognosis in solid tumors. A recent study presented the first evidence that FGFR4 Arg388 could predict resistance to adjuvant chemotherapy in breast cancer. The present study evaluates the potential of this SNP to predict response to neoadjuvant chemotherapy (NCT) for primary breast cancer (PBC).